Character Education Models at School - Yusella, Yeni; Sultoni , Achmad; Suciptaningsih, Oktaviani Adhi (STKIP Yapis Dompu, 2022)
The purpose of writing this article is to find out the concept of character education formulated by experts, the scope of character education in detail, and character education in terms of the scope of character education . The research conducted uses a descriptive analytical method, namely by describing theories according to experts about character education . From the research conducted, it was concluded that the emergence of character education actually showed more of the characters that must be possessed by every student and at the same time the character education strengthened religious education. Character education produce students into creatures who have better characters or values. The success of character education does not depend on whether or not one of the components of education is good or not but rather each other is interrelated and inseparable, so that comes to what is formulated in the purpose of character education. There are some character education learning model inspired by Religious education theory, namely: there are three models of character education, namely